Juridical Analysis of Compensation Settlement for Unlawful Acts in Land Dispute Lawsuits: Case Study of Decision Number 111/PDT.G/2022/PN JMB - Munthe, Eunike Chairani Sukma; Prasetyo, Muhammad Arif (International Journal of Business, Law, and Education, 2025)
An unlawful act is an act that is contrary to the legal norms prevailing in society and can harm other parties. In the context of Indonesian law, this unlawful act is regulated in Article 1365 of the Civil Code (KUHPerdata), which states that "Every act that violates the law and causes harm to another person, requires the person who committed the act to provide compensation." This study aims to legally analyze the settlement of compensation for unlawful acts in land lawsuits, focusing on the study of decision Number 111/PDT.G/2022/PN JMB. Unlawful acts that occur in the context of land disputes often involve losses felt by the injured party, so that regulations regarding compensation are important in the dispute resolution process. In this study, the author examines the legal basis underlying the provision of compensation for unlawful acts and the implementation of applicable legal principles in court. The approach used is the normative research method by analyzing laws and regulations, legal doctrines, and related court decisions. The results of the study show that in decision Number 111/PDT.G/2022/PN JMB, the court has carefully considered the elements of unlawful acts and determined the amount of compensation in accordance with the losses experienced by the plaintiff. This study also reveals the importance of a deep understanding of regulations related to compensation in the context of land cases to ensure justice and legal certainty in resolving land disputes in Indonesia.